When another one bites the dust: environmental impact of global copper demand on local communities in the Atacama mining hotspot as registered by tree rings - Zanetta Colombo, Nicolás; Scharnweber, Tobias; Christie, Duncan A.; Manzano, Carlos A.; Blersch, Mario; Gayo, Eugenia M.; Muñoz, Ariel A.; Fleming, Zoë L.; Nüsser, Marcus (The science of the total environment, 2024)
Assessing the impact of mining activity on the availability of environmental pollutants is crucial for informing health policies in anticipation of future production scenarios of critical minerals essential for the transition to a net-zero carbon society. However, temporal and spatial monitoring is often sparse, and measurements may not extend far enough back in time. In this study, we utilize variations of chemical elements contained in tree-rings collected in local villages from an area heavily affected by copper mining in the Atacama Desert since the early 20th century to evaluate the temporal distribution of pollutants and their relationship with local drivers. By combining time-varying data on local drivers, such as copper production and the dry tailings deposit area, we show how the surge in copper production during the 1990s, fueled by trade liberalization and increased international demand, led to a significant increment in the availability of metal(loid)s related to mining activities on indigenous lands. Our findings suggest that the environmental legislation in Chile may be underestimating the environmental impact of tailing dams in neighboring populations, affecting the well-being of Indigenous Peoples from the Atacama mining hotspot region. We argue that future changes in production rates driven by international demand could have negative repercussions on the environment and local communities. Therefore, mining emissions and the management of tailing dams should be carefully considered to anticipate their potential negative effects on human and ecosystem health.